Understanding Market-Oriented Fashion Concept and Visual Board Practices in Vocational Students - Putri, Farahiyah Inarah (International Journal of Business, Law, and Education, 2025)
This study aims to analyse the level of understanding among 12th-grade students in the Fashion Design vocational program regarding design concepts and their ability to create visual boards, including mood boards, style boards, and market boards. A quantitative descriptive method was employed using a questionnaire consisting of 16 statements, distributed to 85 students. The instrument focused on five key competencies: awareness of the importance of design research, the ability to gather references and analyse trends, idea development, technical skills in board creation, and the utilisation of boards for presentations and portfolios. The results indicate that students’ understanding falls within the moderate to high category. The highest average scores were found in research awareness and concept development (3.16), while the lowest appeared in the use and presentation of visual boards (3.02). Students demonstrated an adequate understanding of design research and visual ideation, but showed limitations in the technical aspects of creating styleboards and in strategic visual communication. These findings suggest the need for more integrative, project-based learning and structured presentation practices. In particular, this study emphasizes students’ understanding of marketboard construction as a reflection of their ability to identify target markets and apply trend forecasting in the conceptualization phase.